Analysis of Animal Models of Myasthenia Gravis Based on Its Clinical Characteristics in Chinese and Western Medicine - CHEN Yuhan; CHEN Jinling; LI Xin; OU Yanhua; WANG Si; CHEN Jingyi; WANG Xingyi; YUAN Jiali; DUAN Yuanyuan; YANG Zhongshan; NIU Haitao (Shiyan dongwu yu bijiao yixue)
Myasthenia gravis (MG) is an autoimmune disease characterized primarily by skeletal muscle weakness and, in severe cases, respiratory involvement. Western medical treatment predominantly relies on immunosuppressants, but long-term administration often leads to notable side effects. In contrast, traditional Chinese medicine (TCM) offers the advantage of multi-target interventions. However, the pathogenesis of MG has not been fully elucidated, and the establishment of animal models that accurately reflect the clinical characteristics of both Chinese and Western medicine is essential for mechanism research and new drug development. This paper systematically reviews the etiology and pathogenesis, diagnostic criteria, and progress of animal model research for MG from both Chinese and Western medicine perspectives. In Western medicine, the pathogenesis of MG is closely related to genetic susceptibility, environmental factors, and autoantibody-mediated postsynaptic membrane damage. In TCM, MG is classified under the category of "flaccidity syndrome", attributed to congenital deficiencies and acquired malnourishment. Western diagnostic criteria involve a combination of clinical symptoms, fatigue testing, serum antibody assays, and electrophysiological evaluation. In contrast, TCM diagnosis emphasizes the integration of primary and secondary symptoms with tongue and pulse pattern differentiation. Currently available animal models mainly include experimental autoimmune myasthenia gravis (EAMG) and passive transfer myasthenia gravis (PTMG). The Toredo acetylcholine receptor (AChR) induced EAMG model aligns well with Western diagnostic criteria, but poorly matches secondary symptoms in TCM. The synthetic AChR peptide model is widely used, but shows low conformity with TCM syndromes. Models induced by muscle-specific tyrosine kinase (MuSK), low-density lipoprotein receptor-related protein 4 (LRP4), and transgenic models demonstrate high innovation but exhibit low clinical conformity. Evaluation of these models requires integration of behavioral, electrophysiological, and immunological indicators. However, a systematic framework for modelling TCM syndromes is still lacking. Future research should integrate TCM-based etiological modelling methods with the Western pathological mechanisms to construct disease-syndrome combination models. Additionally, it is crucial to establish a TCM syndrome evaluation system based on "validation by prescription", as well as to improve the scientific rigor and practicality of animal models by the incorporation of emerging technologies. This review provides a theoretical foundation for optimizing MG animal model design, advancing the research on the combination of Chinese and Western medicine, and supporting efficacy assessment and mechanism exploration of Chinese herbal prescriptions.